2024
DOI: 10.1039/d4py00031e
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of cyclic RAFT agents and ring expansion radical polymerization of vinyl monomers having cyclic topology

Hiroki Ito,
Kota Oto,
Akinori Takasu
et al.

Abstract: In this paper, we describe the synthesis of cyclic vinyl polymers by ring-expansion radical polymerization using a cyclic RAFT agent, which is prepared by bimolecular ring-closing esterification of succinic acid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It is well-known that CTAs can undergo light-initiated degradation, aminolysis, cyclizations, and hydrolysis under certain conditions. Additionally, a few studies have shown that the 4-cyanopentanoic acid group can undergo self-catalyzed hydrolysis to yield an amino adduct. , In one study, Fuchs et al reported the hydrolysis of trithiocarbonates containing this R group and various Z groups (thiododecanyl, thiobutanyl, thioethanyl, and 2-phenyl­(thioethanyl)) and investigated the impact on polymerization control of methyl methacrylate (MMA). Molecular weight and Đ increased with the addition of the amine adduct to pure CTA, indicating a loss of control.…”
mentioning
confidence: 99%
“…It is well-known that CTAs can undergo light-initiated degradation, aminolysis, cyclizations, and hydrolysis under certain conditions. Additionally, a few studies have shown that the 4-cyanopentanoic acid group can undergo self-catalyzed hydrolysis to yield an amino adduct. , In one study, Fuchs et al reported the hydrolysis of trithiocarbonates containing this R group and various Z groups (thiododecanyl, thiobutanyl, thioethanyl, and 2-phenyl­(thioethanyl)) and investigated the impact on polymerization control of methyl methacrylate (MMA). Molecular weight and Đ increased with the addition of the amine adduct to pure CTA, indicating a loss of control.…”
mentioning
confidence: 99%